DESAIN MODEL PEMBELAJARAN PROYEK BERBANTUAN OBS STUDIO PADA MATA KULIAH STUDI WACANA BERORIENTASI PROFIL PELAJAR PANCASILA - Diena San Fauziya; Yusep Ahmadi F (STKIP Siliwangi, 2023)
This research is motivated by the need for learning in discourse studies courses. The purpose of this study was to design a learning model that supports the process of obtaining course learning outcomes that are oriented to the needs of students in the field, as well as to describe the results of model validation and Student Worksheets (SW). The research method used is development research with a 4-D design. Data collection techniques were carried out through document studies, observation, focus group discussions and distributing questionnaires. The model design product was validated by three validators from the fields of learning, IT, and lecturers of discourse studies. SW products are validated by three lecturers and four users from students. Data analysis techniques were carried out using descriptive qualitative and quantitative descriptive. The results obtained, the OBS Studio-assisted project model in discourse studies courses orientated on Pancasila student profiles is suitable for use in learning with the model validation results being in the